Taku Glacier ablation measurements, Alaska. 2014-2016 - Jason Amundson; Martin Truffer (Arctic Data Center, 2018)
This project investigated the feedbacks between glacial erosion and glacier dynamics at Taku Glacier, Alaska, which is currently in the advancing phase of the tidewater glacier cycle. We measured the spatial and temporal patterns of sediment erosion, properties of basal till, basal water pressure, basal motion, ice deformation, surface velocities, surface mass balance, and changes in surface elevation and terminus position. Data was collected from spring 2014 through fall 2016. The project consisted of time-lapse photography, borehole instrumentation, GPS surveys, active seismics, and basic meteorological measurements. All field work was conducted close to the glacier terminus. This data set contains measurements of surface ablation made at several points, which (i) can be used to constrain the meltwater input to the glacier and (ii) is needed for distinguishing changes in surface elevation due to glacier dynamics from those due to climate forcing.